Creative and artistic recreation and a creative approach to recreation organization: a case study of WI-MA Creative Industries Establishments - Mroczek-Żulicka, Aleksandra (Turyzm/Tourism, 2018)
Artistic recreation has been described in the literature for many years as one of its types. However, research into its meaning, or even motivation, is rarely undertaken. The author attempts to confront existing definitions of artistic recreation with changing trends in spending free time and types of recreational activity. She emphasizes the role of a creative approach to the organization of recreation as an opportunity for the better utilization of its potential to affect the development of the individual personality. To illustrate the values of artistic recreation and a creative approach to its organization, the author analyzes the case study of WI-MA Creative Industries Establishments.